2002
DOI: 10.1038/416703a
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cul1–Rbx1–Skp1–F boxSkp2 SCF ubiquitin ligase complex

Abstract: SCF complexes are the largest family of E3 ubiquitin-protein ligases and mediate the ubiquitination of diverse regulatory and signalling proteins. Here we present the crystal structure of the Cul1-Rbx1-Skp1-F boxSkp2 SCF complex, which shows that Cul1 is an elongated protein that consists of a long stalk and a globular domain. The globular domain binds the RING finger protein Rbx1 through an intermolecular beta-sheet, forming a two-subunit catalytic core that recruits the ubiquitin-conjugating enzyme. The long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,440
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,351 publications
(1,487 citation statements)
references
References 50 publications
41
1,440
1
5
Order By: Relevance
“…Most ubiquitination complexes require an E2 conjugating protein to provide the Ub moiety for the E3 ligases or multisubunit E3 ligase complexes (Freemont, 2000;Joazeiro and AM Weissman, 2000;Thrower et al, 2000;Zheng et al, 2002). We found that Smurf2 E3 ligase interacts with RNF11 through its WW domains (Figures 2 and 3).…”
Section: Rnf11 Interacts With Ubch5s But Not With Ubc3mentioning
confidence: 74%
“…Most ubiquitination complexes require an E2 conjugating protein to provide the Ub moiety for the E3 ligases or multisubunit E3 ligase complexes (Freemont, 2000;Joazeiro and AM Weissman, 2000;Thrower et al, 2000;Zheng et al, 2002). We found that Smurf2 E3 ligase interacts with RNF11 through its WW domains (Figures 2 and 3).…”
Section: Rnf11 Interacts With Ubch5s But Not With Ubc3mentioning
confidence: 74%
“…The complex consists of Cul1's Nand C-terminal domains associated non-covalently with each other and with Rbx1. The split Cul1-Rbx1 complex was shown previously to possess the same 3-dimensional structure and ubiquitin ligase activity as the Rbx1 complex with Cul1 expressed as a single polypeptide in insect cells 45 . The 26-residue peptide corresponding to Ubc12's N-terminus, termed Ubc12N26 (sequence MIKLFSLKQQKKEEESAGGTKGSSKK), the five different selenomethionine-substituted Ubc12N26 peptides, and the ScrambledN26 peptide (sequence MKFQLKEIEAGKSKLKSGTSEKGQKS) were chemically synthesized with C-terminal amide blocking groups.…”
Section: Protein and Peptide Preparationmentioning
confidence: 78%
“…A mutant form of APPBP1-UBA3 lacking APPBP1's 254-258 loop and UBA3's N-terminal 11 residues, with UBA3's catalytic Cys216 mutated to Ala was used for crystallization 26 . Biochemical studies used full-length, wild-type E1s 44,45,28 or APPBP1-UBA3 mutants expressed and purified as for the wild-type E1; wild-type or mutant versions of Ubc12 28 as indicated; and the truncated active versions of ubiquitin and the UBLs human NEDD8 and S. cerevisiae Sumo (Smt3p) terminating with the sequence Gly-Gly44 , 26 , 28. The human Rbx1-Cul1 (split) complex was obtained in soluble form from E. coli by simultaneously coexpressing Rbx1, Cul1's N-terminal domain (residues 1-411), and Cul1's C-terminal domain (residues 411-776 at the C-terminus).…”
Section: Protein and Peptide Preparationmentioning
confidence: 99%
“…The SCF-type E3 ligase is typically composed of four different polypeptides: SKP1 that serves as an adaptor protein; Cullin1 (CDC53); RING-finger protein RBX1 (or ROC1 and HRT1) that interacts with the Cullin1 and E2-conjugating enzyme; and an F-box protein that is responsible for recruiting substrates. Structural analysis indicated that Cullin1 (most of the time abbreviated as CUL1) acts as a scaffold that directs other members of the SCF complex to bring the ubiquitin-loaded E2s and the substrate in proximity to promote the transferring of ubiquitin directly from the E2 to the substrates [26]. Besides Cullin1, recent data indicated that Cullin2 and Cullin3 also form similar groups of E3 ligases, in which an elongin C-SOCS module or a BTB protein replaces the SKP1-F-box protein module npg in the Cullin1-type SCF E3 ligase, respectively [27][28][29].…”
Section: Diversity Of Plant E3 Ligasesmentioning
confidence: 99%